Facilitating Applied Learning in an Introductory Course on Exceptionalities through a Student Choice Project - Heidi R. Cornell; Jennifer P. Stone (The Advocate, 2017)
Many beginning teachers feel unprepared to teach students in their inclusive classrooms. Preservice teachers may need applied learning experiences, intentionally focused on understanding of individuals with disabilities as human rather than as their disability or label. This paper shares an applied learning project couched in the principles of Universal Design for learning completed by students in a course about disabilities. Two Student Choice Project examples are shared to demonstrate the process for completion and to provide preliminary evidence of how this project facilitated transformation of student perceptions, built awareness, and improved openness and objectivity in understanding individuals with disabilities.
Keywords: applied learning; student choice; exceptionalities; disability; teacher education